Analysis of Mathematical Connection Ability and Mathematical Disposition Students of 11th Grade Vocational High School - Setiawan, Fajar Tri; Suyitno, Hardi; Susilo, Bambang Eko (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was to described mathematical connection ability, mathematical disposition students of eleventh grade Vocational High School. This research also was to described mathematical connection ability reviewed by mathematical disposition and mathematical disposition reviewed by mathematical connection ability. The social situation was students of eleventh grade Eight Vocational High School. The subject in this research was students in the level of capacity to mathematical connection ability and mathematical disposition was three students in XI RPL 2 Eight State Vocational High School of Semarang. The result showed a description (1) mathematical connection ability level of students were medium; (2) mathematical disposition level of students were medium; (3) students had high mathematical connection ability level tendency to construct mathematical disposition level better than students had medium and low mathematical connection ability level; (4) students had high mathematical disposition level tendency to construct mathematical connection ability level better than students had medium and low mathematical disposition level.